Transcription factors and complex disease development - Pineda-Torra, Ines (Henry Stewart Talks, 2014)
Transcription factors (TFs): function and role in disease, Identified transcription factor variants and impact on CVD and Type 2 diabetes disease risk, Traditional approaches (gene candidate studies, e.g. PPARgamma), Contemporary approaches (genome wide association studies, e.g. TCF7L2, SORT1), Study of functionality of transcription factor mutations